2008
DOI: 10.1007/s10902-008-9119-0
|View full text |Cite
|
Sign up to set email alerts
|

Job Insecurity and Well-Being: Moderation by Employability

Abstract: Job insecurity, Perceived employability, Well-being,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
236
2
14

Year Published

2010
2010
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 253 publications
(270 citation statements)
references
References 50 publications
18
236
2
14
Order By: Relevance
“…employed or unemployed (Jiang et al, 2012), full-time or part-time employment (Berger, 2009)). Employees usually seek for employment security (Silla, De Cuyper, Gracia, Peiró, & De Witte, 2009). Unemployment status makes people unhappy (Escott & Buckner, 2013).…”
Section: Employment Statusmentioning
confidence: 99%
“…employed or unemployed (Jiang et al, 2012), full-time or part-time employment (Berger, 2009)). Employees usually seek for employment security (Silla, De Cuyper, Gracia, Peiró, & De Witte, 2009). Unemployment status makes people unhappy (Escott & Buckner, 2013).…”
Section: Employment Statusmentioning
confidence: 99%
“…(23) As mentioned above, buffers against insecurity and strain may be found in social support in the workplace, (24) and perceived employability. (25) However, the inequities of nonstandard employment are often exacerbated because those workers tend to have lower education, be in low skill occupations and lack the previously mentioned resources. (26)(27)(28) Consequently, some researchers have advocated for a greater recognition of the political, social and labour market contexts determining relationships between employment and health.…”
Section: Pathways From Nonstandard Employment To Healthmentioning
confidence: 99%
“…A few studies have identified additional work-related behaviors such as increased job search behavior (Adkins, Werbel, & Farh, 2001;Reisel & Banai, 2002) or safety (Probst & Brubaker, 2001). Other study by Silla et al (2008) suggests that job insecurity related to poor well-being.…”
Section: National Institute Of Occupational Safety and Health (Niosh)mentioning
confidence: 99%